Treatment of Depression With Psychotic Features in Maltreated Adolescents: Evidence-Based Case Report - Setiawan, Feronia Augustine; Phernando, Nicholas Kevin; Ulya, Zuhrotun (Faculty of Medicine, Universitas Airlangga, 2023)
Introductions: Depressive disorders are expected consequences of experiencing child maltreatment. Many depressive disorders can occur with or without psychosis, which has different implications for treatment and prognosis. This condition raises the challenge of treating depression in maltreated adolescents because the patient has inadequate family and social support. Consequently, it is difficult for the patient to undergo psychotherapy that involves family. Case: A 17-year-old female was diagnosed with psychotic depression. The patient had symptoms of depression, accompanied by hallucinations, since five years ago. The patient was hospitalized for suicidal ideation and food refusal for days. Patient had a history of child maltreatment by family and experienced bullying since elementary school. Patient believes that her family, especially her mother, had hated her from the beginning. Discussions: After stabilization of the patient's general condition, psychopathology exploration was done together with selection of appropriate treatment. Combined Cognitive Behavioral Therapy (CBT), Selective Serotonin Reuptake Inhibitor (SSRI) and atypical antipsychotic treatment are the evidence-based treatments for psychotic depression in maltreated adolescents. Studies involving patients with psychotic depression which were treated by combination of sertraline and olanzapine showed significant improvement of depression and psychotic symptoms and reduced the risk of relapse over 36 weeks, compared to sertraline plus placebo. Conclusion: Combination of SSRI, atypical antipsychotic and CBT with a trauma-informed approach should be considered as treatment for psychotic depression in maltreated adolescents.